THE IMPACT OF SPORTS ON STUDENT LIFE - Umarova Zulxumor Urinboyevna; Umarov Yunusxon Yokubjon o’g’li (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
This article discusses the general concept of sports, how sports affect the general condition of a student, what a student can achieve by doing sports. Regular physical education and sports activities are offered to improve the health of students, their impact on students and their importance in the educational process are studied.